A discourse of education as a prime factor for the development of a nation: contributions of Islamic scholars in Nigeria - Kayode, Bakare Kazeem; Salleh, Mohamad Johdi (2009)
Development of any nation both in the past and present is premised on the development of her human intellectual capabilities. The growth in the rational thinking of man enables him to develop creative means of understanding his environment to satisfy both individual and collective needs of the society. Satisfying identified needs and discovering of the latent needs by man gradually metamorphous into development of a nation. As human advances from old sociological history to new, the dimensions of life, culture, perspectives of society and nation undergo radical changes. These changes occur in the light of discarding the old methods or style of thinking and reasoning to a more advance ways; which are more compatible with the present environmental challenges. Response of man to his environmental stimuli in different parts of the world has often results into recovery of man and society from sour dictates of nature. It’s also resulted into rapid building and rebuilding different nation of the world.